SOSIALISASI PENGEMBANGAN KEPROFESIAN BERKELANJUTAN (PKB) UNTUK GURU SEKOLAH DASAR - Tri Wiyoko; Randi Eka Putra; Puput Wahyu Hidayat; Zulqoidi R Habibie; Tri Wera Agrita (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2022)
This service activity aims to socialize the competence of Continuous Professional Development (PKB) for elementary school teachers. The method of implementing this activity is by using lectures and discussions. The activity was carried out at SD Negeri 90/II Muara Bungo. The results of the evaluation of service activities show that the implementation of service activities is able to provide solutions to existing problems of 3.5% in the very good category. participants' satisfaction with the delivery of material that meets their needs is 3.35%. Satisfaction with the PkM implementation method is 3.64% with very good criteria. Overall satisfaction in implementing this PkM is 3.21% with good category. Thus, service activities make teachers increase their knowledge and abilities in preparing Continuing Professional Development (PKB) in the form of classroom action research, changing research results in scientific journal articles. In addition, the teacher's ability is also able to find and examine scientific references well.